2016
DOI: 10.1093/alcalc/agw078
|View full text |Cite
|
Sign up to set email alerts
|

Internet Support for Dealing with Problematic Alcohol Use: A Survey of theSoberistasOnline Community

Abstract: AimsAdvances in technology have led to an increased range of possibilities for forms of mutual aid in addictions, and patient empowerment in the management of long-term conditions. However, the effective processes involved may be different online than for those that meet in person. Soberistas is a ‘social network site for people who are trying to resolve their problematic drinking patterns’. We aim to describe the population, component parts and processes that define this online community, and consider potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 27 publications
(36 reference statements)
0
39
0
Order By: Relevance
“…For instance, a survey of members of an online social network site for women trying to resolve alcohol problems revealed that 47% of the site’s members had never tried any other form of support related to their drinking. 79 A large survey study in the United Kingdom showed that women were more likely than men to use online recovery groups (but not recovery websites or apps). 80 A separate study examining use of one social network site for SUD recovery also found a higher proportion of women than men using the site.…”
Section: Gender Differences In Treatment Entry Retention and Outcommentioning
confidence: 99%
“…For instance, a survey of members of an online social network site for women trying to resolve alcohol problems revealed that 47% of the site’s members had never tried any other form of support related to their drinking. 79 A large survey study in the United Kingdom showed that women were more likely than men to use online recovery groups (but not recovery websites or apps). 80 A separate study examining use of one social network site for SUD recovery also found a higher proportion of women than men using the site.…”
Section: Gender Differences In Treatment Entry Retention and Outcommentioning
confidence: 99%
“…It is possible that this cohort has more confidence in selecting and assessing information and therefore felt more at ease with rejecting group beliefs that did not appear true to them. However, high levels of education amongst study participants have been noted in several studies of users of non-12-step alcohol support groups, e.g., [7,28]. It is possible that the interviewees studied here are in fact representative of active users of these groups.…”
Section: Limitations Of the Studymentioning
confidence: 83%
“…Best et al (2015) demonstrated that males and females often have differing recovery pathways; particularly, men favor Alcoholics Anonymous more than females (Alcoholics Anonymous, 2012; Kelly & Hoeppner, 2013). Sinclair, Chambers & Manson (2017) surveyed members of Soberistas (Rocca, 2016), a social network site primarily aimed at women trying to resolve alcohol problems, finding that of the 438 women taking part in the crosssectional survey, 46.5% reported they had not tried any other forms of support, suggesting that for these women the flexibility that this platform offered in terms of engagement and anonymity helped foster alcohol free identities. Feminist research (Staddon, 2005) supports the notion that offline groups such as AA merely reflect the patriarchal structure of society in micro, which partially explains the attraction of Soberistas for some women.…”
Section: Gender Differences In Recoverymentioning
confidence: 99%